Methodological framework project management. (Journal of Economic Research & Business Administration, 2015)
The author examines the most common project management methodology in the world. A comparative analysis of existing in the world of project management methodologies. Many international and national project management methodology are advisory in nature. This means that not necessarily use all of the processes described in a particular methodology. Regardless of what the level of maturity at the project management organization or a company, they can be used either completely or partially. Identified components of project management methodologies and the basic principles of design methodologies. The article recommended using described therein components and principles of design methodology choose the one project management methodology that best suited to the specifics of your business.
Keywords: project management; project; principles of project management methodological project management PMBOK; ISO 21500; project management standards